Effect of group-based nutritional education combined with individual standard care for outpatients with type 2 diabetes: study protocol for a randomized clinical trial {1} - Aline Busanello; Vanessa Machado Menezes; Olivia Garbin Koller; Ândria Völz Andreia; Jussara Carnevale de Almeida (Trials)
Abstract Background Diabetes remains a significant contributor to global morbidity and mortality in the twenty-first century. Lifestyle modification strategies are widely recommended for effective diabetes management. Research suggests that a person-centered approach, implemented in either group or individual settings, offers considerable potential for improving long-term disease outcomes. Nutritional counseling using the operative group model has been tested and shown to yield positive health outcomes across diverse populations affected by diabetes. This study aims to evaluate the impact of group-based nutritional education, combined with individual standard care, compared to individual standard care alone, on health outcomes among patients diagnosed with type 2 diabetes. Methods This study is a 12-month, parallel-group, randomized superiority controlled trial. Individuals diagnosed with type 2 diabetes will be randomized in a 1:1 ratio into one of two treatment arms: (1) individual usual care alone or (2) usual care supplemented with group-based nutritional education. The group nutritional education will consist of three sessions addressing the following themes: “Let’s Go Shopping,” “Healthy Plate,” and “Hunger and Satiety.” The primary outcome will be the change in HbA1c levels. Secondary outcomes will include fasting glucose, lipid profile, body mass, dinapenic abdominal obesity, blood pressure, eating behavior, adherence to nutritional counseling, and diabetes-related complications. All outcomes will be assessed at baseline and at 4, 8, and 12 months, except diabetes-related complications that will be assessed at baseline and 12 months. Sample size calculations were based on an estimated mean difference of 0.59 ± 1.39% in HbA1c with the intervention (patient-centered group), using a type I error rate of 5% and a type II error rate of 20%. It was determined that 88 participants per group (1:1 randomization; n = 176) would provide sufficient statistical power. Accounting for an anticipated dropout rate of 30%, a total of 252 participants will be recruited to ensure the necessary sample size is maintained throughout the study period. Discussion The American Diabetes Association recommends interventions for patients with diabetes lasting more than 10 h over a period of 6 to 12 months to optimize health outcomes. Therefore, this study hypothesizes that integrating group-based nutritional education into standard treatment within a nutrition-specialized outpatient clinic may lead to further improvements in health parameters among individuals diagnosed with type 2 diabetes mellitus. Trial registration {2a and 2b} Clinicaltrials.gov identifier, NCT05598203. Registered on 13 October 2022.